Practical cataloguing with AACR-II - Mohd. Sabir Husain (Ess Ess publications, 2018)
Cataloguing is an essential process that provides access to all acquired information resources of the library by allowing people to find information needed for their personal and professional growth and development. Realizing the need and importance of cataloguing in library management, this book deals with the practical aspects of cataloguing by AACR-II. The book simplifies the preparation of various kinds of entries of different forms of documents generally available in libraries for use. This book covers the fundamental aspects of cataloguing rules and forms of entries, and it provides a number of examples of various cataloguing problems which include simple authors, corporate authors, pseudonyms, and sacred scriptures. This book will be of immense use to LIS students and library professionals.